Livestock-environment interactions under intensifying production - Staal, Steven J.; Ehui, Simeon K.; Tanner, J.C. (CAB International, 2001)
As human populations continue to grow, the intensification of agricultural production is occurring in order to maintain food consumption and rural income levels in developing countries. The demand for livestock products is generally income-elastic, so that, with increases in real incomes in most regions, the demand for livestock products is growing as well, resulting in greater projected numbers of both ruminant and monogastric livestock. Both trends and, indeed, their interaction will have consequences for rural and urban environments in the future and for the sustainability of land-use systems. The intensification of agricultural land use may degrade soils and alter natural habitats and biodiversity or, in some cases, may lead to excessive levels of inputs, with consequent effects on the environment. Similarly, increased livestock production may lead to animal-waste pollution in some settings, and contribute to greenhouse-gas production. What may not be well recognized, however, is the role that ruminant livestock, in particular, play in assisting the attainment of higher and more sustained levels of agricultural production, often in ways that have net positive environmental impacts. This role is particularly important in the crop-livestock systems on which (sub)tropical agricultural production is increasingly dependent. 'Win-win' situations are clearly possible, especially through the contribution of intensive livestock production to soil fertility, which is relevant for large areas of the world, where soil nutrient deficits and slow nutrient turnover rates remain the primary agricultural constraint. This chapter begins by describing the relative importance of different livestock production systems and the global trends associated with them. Within each system, the net impact of livestock production on the environment is discussed and case studies of positive livestock and environment interactions are presented. Finally, the possibilities for and implications of further intensification of livestock production are explored in some depth.